Trinity: Visual dramaturgy, the body as scenographer and author. Issue 2 (1st December 2019) - Lane, Kate
This visual essay will introduce Brave New Worlds' costume-led devising process in the creative evolution of their production, Trinity. Brave New Worlds is a collaboration between movement specialist and director Valentina Ceschi, and artists and scenographers Guoda Jaruseviciute and myself, Kate Lane. Their work centres on the body as scenographer and on collective authorship of design and direction and examines the following research questions: How can a costume direct the body's movement and this movement direct the design development? How do you create a dramaturgy from the scenography, invoking concept and narrative? If body scenography is the central focus for the performance, how do other design aspects collaborate to create a complete scenographic experience? This visual essay will present the working methodology of a visual dramaturgy, examining the use of the body as the instigator in the scenography, the dialogue between the costume and the performer, and between the designer/performer as subject, author and object of the design. It will explore the stages of production, and creative processes involved, from initial research on concept through design development to the implications of site-specific locations on the scenography and final dramaturgy. In the process, it places costume as author and dramaturg.